Multisensory integration facilitates perceptual restoration of an interrupted call in a species of frog. (3rd June 2022) - Zhu, Bicheng; Yang, Yue; Zhou, Ya; Deng, Ke; Wang, Tongliang; Wang, Jichao; Tang, Yezhong; Ryan, Michael J; Cui, Jianguo
Abstract: Communication signals by both human and non-human animals are often interrupted in nature. One advantage of multimodal cues is to maintain the salience of interrupted signals. We studied a frog that naturally can have silent gaps within its call. Using video/audio-playbacks, we presented females with interrupted mating calls with or without a simultaneous dynamic (i.e., inflating and deflating) vocal sac and tested whether multisensory cues (noise and/or dynamic vocal sac) inserted into the gap can compensate an interrupted call. We found that neither inserting white noise into the silent gap of an interrupted call nor displaying the dynamic vocal sac in that same gap restored the attraction of the call equivalent to that of a complete call. Simultaneously presenting a dynamic vocal sac along with noise in the gap, however, compensated the interrupted call, making it as attractive as a complete call. Our results demonstrate that the dynamic visual sac compensates for noise interference. Such novel multisensory integration suggests that multimodal cues can provide insurance against imperfect sender coding in a noisy environment, and the communication benefits to the receiver from multisensory integration may be an important selective force favoring multimodal signal evolution.